Craniopharyngiomas Presenting with Nonobstructive Hydrocephalus: Underlying Influence of Subarachnoidal Hemorrhage. Two Case Reports - Kawaguchi, Tomohiro; Ogawa, Yoshikazu; Watanabe, Mika; Tominaga, Teiji (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Nonobstructive hydrocephalus in craniopharyngioma patients is rare, and the etiology is not known. We report two cases of patients with craniopharyngioma who presented with nonobstructive hydrocephalus. Repeated subarachnoidal hemorrhage (SAH) was considered as the underlying mechanism of hydrocephalus development. The first case was a 67-year-old woman presenting with deteriorated consciousness. Head computed tomography (CT) and magnetic resonance (MR) imaging demonstrated a solid suprasellar tumor with subarachnoidal and intraventricular hematoma with ventricle dilatation but no cerebrospinal fluid (CSF) obstruction. The extended transsphenoidal approach achieved gross total removal. Because of persistent ventricle dilatation, ventriculoperitoneal shunt was required. The second case was a 35-year-old woman presenting with persistent headache. Head CT and MR imaging demonstrated a solid suprasellar tumor with ventricular dilatation but no CSF obstruction. The extended transsphenoidal approach achieved gross total removal. The postoperative course was uneventful, and a ventriculoperitoneal shunt was not required. In both cases, histologic examination of the tumors revealed squamous-papillary type craniopharyngioma with remarkable inflammatory cell infiltrations in the perivascular space. CSF cytology revealed hemosiderin-laden phagocytes, indicative of previous SAH causing CSF malabsorption. These cases suggested that surgery should be indicated for patients with craniopharyngiomas with nonobstructive hydrocephalus, even if the tumors are not associated with neurologic and/or endocrinologic deficits.
Keywords: craniopharyngioma; communicating hydrocephalus; subarachnoid hemorrhage; cerebrospinal fluid; malabsorption